2020
DOI: 10.3390/nu12051437
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroendocrine Neoplasms of the Digestive Tract: Diagnosis, Treatment and Nutrition

Abstract: Nuroendocrine neoplasms (NENs) are a group of rare neoplasms originating from dispersed neuroendocrine cells, mainly of the digestive and respiratory tract, showing characteristic histology and immunoprofile contributing to classification of NENs. Some NENs have the ability to produce biogenic amines and peptide hormones, which may be associated with clinical syndromes like, e.g., the carcinoid syndrome caused by unmetabolized overproduced serotonin, hypoglycemic syndrome in case of insulinoma, or Zollinger-El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 106 publications
(178 reference statements)
0
24
0
2
Order By: Relevance
“…In addition, CgA is a soluble secretory glycoprotein secreted by dense-core secretory of neuroendocrine cells [ 28 , 29 , 30 ], and it has been found that 60% to 80% of NENs in the digestive system contain elevated serum CgA levels [ 31 , 32 , 33 ]. Serum CgA is related to tumor burden, and the serial measurement of CgA may be useful to detect recurrence [ 29 , 34 ]. In a previous study involving 44 patients with NENs, the sensitivity and specificity of CgA for detecting NEN were 86% and 88%, respectively [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CgA is a soluble secretory glycoprotein secreted by dense-core secretory of neuroendocrine cells [ 28 , 29 , 30 ], and it has been found that 60% to 80% of NENs in the digestive system contain elevated serum CgA levels [ 31 , 32 , 33 ]. Serum CgA is related to tumor burden, and the serial measurement of CgA may be useful to detect recurrence [ 29 , 34 ]. In a previous study involving 44 patients with NENs, the sensitivity and specificity of CgA for detecting NEN were 86% and 88%, respectively [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recommendations also focus on the limitation of the consumption of fat to 30%, especially in people with a carcinoid and a tendency to have diarrhea [36]. However, it is highlighted that a diet's constituents should be individually adjusted to the needs of the patient [37]. Moreover, NEN patients with hypersensitivity should be wary of certain products that feature biogenic amines [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is highlighted that a diet's constituents should be individually adjusted to the needs of the patient [37]. Moreover, NEN patients with hypersensitivity should be wary of certain products that feature biogenic amines [37]. Products that they should avoid include, e.g., ripe cheese, smoked meat, alcohol-wine/beer, soy products, broad bean, sauerkraut, tomatoes, avocados, bananas, raspberries, pineapples and chocolate [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequently occurring caloric restrictions in the use of vegetarian diets have an effect on life extension and protection against cancer [ 7 ]. Likewise, eliminating fried, smoked, or grilled foods, red meat, aflatoxin-contaminated foods, preserved salty meals, and alcohol [ 8 ]. Moreover, cancer risk is also reduced by introducing a diet rich in plant foods (e.g., vegetables, beans, fruit, and whole grains) and by reducing consumption of animal fat, meat, and fatty dairy products [ 9 ].…”
Section: Introductionmentioning
confidence: 99%